The Effect of Green Spaces on Housing Prices Using Hedonic Method in Iran - Gholamhosein Moradi; Elham Operajuneghani; Farnaz Dehghan Benadkuki; Sajad Ghanbari; Mostafa Moradi (Environmental Resources Research, 2022)
Nowadays, the housing market and related issues are global matters that have attracted the attention of planners and policymakers. So housing price estimation is Fundamental for public and private investors. The environmental characteristics of a place, such as green space, are one of the determining factors in housing prices. Therefore, this research has been conducted to investigate the effect of green space on the price of surrounding houses in the Ghadir park of Yazd in central Iran. The sample size was determined using Cochran relation. The data have been collected by a questionnaire, referring to real estate agencies and maps. The ordinary least squares regression method and Eviews 9 software were used to analyze the data. Then, a model was proposed for estimating the hedonic price function of the study area. According to the results, from 15 independent variables, variables of reconstruction, number of floors, number of bedrooms, distance to the main street, distance to the city center, and distance to park have a significant relationship with the price of housing units (P≤0.05). The adjusted coefficient of determination (R2) was equal to 0.918. Using the hedonic method, it is concluded that although environmental goods such as parks and green spaces are not exchanged in the market, families pay for them in reality.